Measurements of charm mixing and violation using decays - Aaij, R; Adeva, B; Adinolfi, M; Ajaltouni, Z; Akar, S; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; Alves, AA; et al. (American Physical Society, 2017)
Measurements of charm mixing and CP violation parameters from the decay-time-dependent ratio of D0K+π- to D0K-π+ decay rates and the charge-conjugate ratio are reported. The analysis uses &Bmacr;D*+μ-X, and charge-conjugate decays, where D*+D0π+, and D0K∓π±. The pp collision data are recorded by the LHCb experiment at center-of-mass energies √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb-1. The data are analyzed under three hypotheses: (i) mixing assuming CP symmetry, (ii) mixing assuming no direct CP violation in the Cabibbo-favored or doubly Cabibbo-suppressed decay amplitudes, and (iii) mixing allowing either direct CP violation and/or CP violation in the superpositions of flavor eigenstates defining the mass eigenstates. The data are also combined with those from a previous LHCb study of D0Kπ decays from a disjoint set of D*+ candidates produced directly in pp collisions. In all cases, the data are consistent with the hypothesis of CP symmetry.